2019
DOI: 10.1002/cem.3162
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of undesirable deviations in must fermentation using a portable FTIR‐ATR instrument and multivariate analysis

Abstract: A portable FTIR-ATR spectrometer was used to monitor small-scale must fermentations (microvinifications) with the aims to describe the process and to early detect problematic fermentations. Twenty fermentations at normal operation conditions (NOC) and three fermentations that were intentionally deviated from NOC (yeast assimilable nitrogen deficiency-YAN) were monitored. FTIR-ATR spectra were registered after a minimum sample pretreatment during the fermentation process. In addition, density, sugars (glucose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The spectra were acquired with the Microlab PC software (Agilent, CA, USA) using a methodology previously optimized [21], that is, measuring from 4000 to 650 cm −1 , with 32 scans and 8 cm −1 resolution.…”
Section: Mid-infrared Spectroscopic Analysismentioning
confidence: 99%
“…The spectra were acquired with the Microlab PC software (Agilent, CA, USA) using a methodology previously optimized [21], that is, measuring from 4000 to 650 cm −1 , with 32 scans and 8 cm −1 resolution.…”
Section: Mid-infrared Spectroscopic Analysismentioning
confidence: 99%
“…To the best of our knowledge, limited studies have been performed to evaluate the abilities of portable and hand-held FTIR systems to be used for quality control in the wine process from farm to fork. In one of these studies, Cavaglia et al [55] employed a portable FTIR-ATR spectrometer combined with PCA and PLSR multivariate statistics to monitor the fermentation process to detect microvinifications and defective fermentations in the fermentation process. According to their results, ATR-FTIR spectroscopy combined with chemometrics has the ability to be used for the early detection of fermentation defects with at-line application possibilities.…”
Section: Implementation Of Portable and Hand-held Ftir Spectroscopy T...mentioning
confidence: 99%
“…Several models have been developed to monitor the evolution of fermentation and, at the same time, discriminate between normal and problematic fermentations. The outcomes showed that the method could be applied in the wine industry for monitoring the sugar content and identifying nutrient deficiencies early (Cavaglia et al, 2019). Spectra coming from a portable ATR-MIR device and multivariate analysis were used to control the alcoholic fermentation process and detect wine fermentation problems.…”
Section: Determination Of Basic Oenological Parametersmentioning
confidence: 99%